Comments and Reply on: "Study of multi-muon events produced in p (p)over-bar interactions at root s=1.96 TeV"; T. Aaltonen et al. (The CDF Collaboration) - Bethke, S; Aaltonen, T; Adelman, J; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
The European Physical Journal C-Particles and Fields-publishes scientific manuscripts of relevance to the scientific community following careful and strict peer reviewing and, whenever appropriate and necessary, through discussion with the authors, so as to optimise scientific content and style of presentation prior to publication. In some cases significant disagreement between authors and referees (and/or editors) of the journal cannot be resolved despite all efforts and best of intentions. While the journal-notwithstanding any appeals-retains the right to reject such manuscripts, the editors of this journal may decide, in cases deemed of exceptional interest and potential significance for the field, to accept the manuscript for publication, to amend it by "comments" of the editor(s) in charge and, if appropriate, by a "reply" of the authors of the commented manuscript. The present comment is on "Study of multi-muon events produced in pp̄ interactions at √ = 1.96 TeV"; T. Aaltonen et al. (The CDF Collaboration, Eur. Phys. J. C, 2010, doi:10.1140/epjc/s10052-010-1336-0. © 2010 The Author(s).